Silent spring - Carson, Rachel, 1907-1964 (Houghton Mifflin, 2002)
"This fortieth anniversary edition celebrates Rachel Carson's watershed book with new essays by the author and scientist Edward O. Wilson and the acclaimed biographer Linda Lear, who tells the story of Carson's courageous defense of her truths in the face of ruthless assault from the chemical industry in 1963, the year following the publication of Silent Spring and before her untimely death. First published by Houghton Mifflin in 1962, Silent Spring alerted a large audience to the environmental and human dangers of indiscriminate use of pesticides, spurring revolutionary changes in the laws affecting our air, land, and water. "Silent Spring became a runaway bestseller, with international reverberations . . . [It is] well crafted, fearless and succinct . . . Even if she had not inspired a generation of activists, Carson would prevail as one of the greatest nature writers in American letters" (Peter Matthiessen, for Time's 100 Most Influential People of the Century).